2021
DOI: 10.9734/jpri/2021/v33i24b31438
|View full text |Cite
|
Sign up to set email alerts
|

Population Awareness and Attitude towards First Aid in Burn in Makkah Al-Mukarramah, Saudi Arabia – A Cross Sectional Study

Abstract: Background: Worldwide, an estimated 180, 000 deaths per year are caused by burns. Majority occur in low- and middle-income countries. Inadequate awareness of burn first aid has been reported in both developed and developing countries. In Saudi Arabia, studies reported inadequate level of knowledge of general population of first aid in burns emergencies including communities of Al-Madinah Al-Munawwarah, Jeddah, Riyadh, Majmaah and Hail. Objective: we aim to assess the general knowledge and attitude regrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Almost two-thirds of these occurrences occur in the WHO regions of Africa and Southeast Asia, with the majority occurring in low- and middle-income countries [ 5 ]. The observed situation is made worse by the fact that Saudi Arabia has weak burn first-aid practices and a significant prevalence of traditional home remedies [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost two-thirds of these occurrences occur in the WHO regions of Africa and Southeast Asia, with the majority occurring in low- and middle-income countries [ 5 ]. The observed situation is made worse by the fact that Saudi Arabia has weak burn first-aid practices and a significant prevalence of traditional home remedies [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Almost two-thirds of these occurrences occur in the WHO regions of Africa and Southeast Asia, with the majority occurring in low-and middle-income countries [5]. The observed situation is made worse by the fact that Saudi Arabia has weak burn first-aid practices and a significant prevalence of traditional home remedies [6,7]. Saudi Arabian respondents to a study conducted in Majmaah reported having limited knowledge of first aid despite possessing bachelor's degrees and being generally well-educated [7].…”
Section: Introductionmentioning
confidence: 99%
“…Factors influencing caregivers during an exercise-based rehabilitation program for pediatric burn injuries must be identified. 16 The study of caregivers’ knowledge of physiotherapy, attitude towards physiotherapy, adherence to the prescribed program, and satisfaction may aid in the development of a comprehensive education program for caregivers and, as a result, improve the success of pediatric burn rehabilitation programs. The objective of this study was to determine the caregivers’ basic knowledge and attitude towards physiotherapy-related management of pediatric burns, assess the caregiver burden, and adhere to the exercise program.…”
Section: Introductionmentioning
confidence: 99%